Orthogonal systems and convolution operators - Ellis Robert L; Gohberg Israel (Basel Birkhauser Verlag, 2003)
The main concern of this book is the distribution of zeros of polynomials that are orthogonal on the unit circle with respect to an indefinite weighted scalar or inner product. The first theorem of this type, proved by M. G. Krein, was a far-reaching gen
Keywords: Operator theory